Early MDO with a Virtually Planned Distractor in a Neonate with Pierre Robin Sequence - Lutz, Rainer; Olmos, Manuel; Schmidt, Joachim; Morhart, Patrick; Nobis, Christopher-Philipp; Möst, Tobias; Kesting, Marco Rainer; Weber, Manuel (Plastic and Reconstructive Surgery Global Open, 2022)
Pierre Robin sequence (PRS) is characterized by mandibular micrognathia, glossoptosis, and airway obstruction. We report a case of a female infant with PRS in combination with deletion of chromosome 4q and cardiac insufficiency due to an atrioventricular septum defect. The child was transferred to our center from a peripheral hospital with respiratory insufficiency. Initially, respiration was ensured using a continuous positive airway pressure (CPAP) device because a Tuebingen plate was not tolerated. After a pediatric cardiac surgery intervention, CPAP ventilation proved to be insufficient, and the young patient had to be resuscitated and endotracheal intubation was required for recurrent severe respiratory failure. To avoid tracheostomy, an interdisciplinary decision was made to perform an early mandibular distraction. In the fifth week of life, two patient-specific internal distractors were implanted after prior virtual surgery planning. This approach allows for shorter surgical time through preoperative vector planning and fabrication of a patient-specific distractor, in combination with reduced morbidity through maximum protection of adjacent structures such as the tooth follicles and inferior alveolar nerves. An advancement of the mandible by 15mm could be achieved within 2 weeks. Thereafter, the small patient could be extubated successfully, and there was no further episode of major respiratory insufficiency. We demonstrate that mandibular early distraction with a patient-specific distractor is a successful method to treat severe respiratory insufficiency in PRS, and it can prevent the necessity for tracheostomy with the resulting disadvantages. We provide details concerning our therapeutic algorithm, metric analyses, and a discussion of relevant literature.
CRIS-Team WoS Importer:2022-06-17